The National Library in the Era of Digital Libraries : The Remote Access/Delivery of the National Central Library - Sung, C-C (Tʻu shu kuan hsüeh yü tzŭ hsün kʻo hsüeh, 1997)
For several years, the National Central Library (NCL) has been actively promoting digitalization. It has been storing the library's substantial collection of academic journals, government documents, and literary and historical materials on databases so they can be easily accessed through networks by readers in Taiwan and abroad. This service is known as the "Remote Electronic Access / Delivery of the National Central Library" (READncl). READncl features nine systems with over one million entries, nearly three million pages of text images on 181 CD-ROMs, 246 full-text hyperlinked periodicals, and also links to the home-pages and e-mail addresses of 160 publishers, 142 government agencies, and 50 libraries. READncl is a service combining bibliographic search, book lending and subject query functions. READncl can provide not only the bibliographic index data, but also the capability to read and print full texts. At the current stage, NCL goes on to establish full-text image and bibliographic databases for the internal publications in three categories : Periodical resources, Governmental information, and Literature/Art. At the second stage, NCL will encourage collaborative efforts between librarianship and the publishing professions to establish digital databases and to provide digitalized learning resources for the epoch of the information age to come.